PSSA : parallel stretched simulated annealing - Ribeiro, Tiago Filipe Rodrigues (2013)
We consider the problem of finding all the global (and some local) minimizers of a given nonlinear optimization function (a class of problems also known as multi-local programming problems), using a novel approach based on Parallel Computing. The approach, named Parallel Stretched Simulated Annealing (PSSA), combines simulated annealing with stretching function technique, in a parallel execution environment. Our PSSA software allows to increase the resolution of the search domains (thus facilitating the discovery of new solutions) while keeping the search time bounded. The software was tested with a set of well known problems and some numerical results are presented.